Universal energy access: moving from technological fix to poverty reduction - Oliver Johnson (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Despite much progress in expanding energy systems in developing countries, an estimated 1.3 billion people do not have access to electricity, and around 2.8 billion people do not have access to clean cooking facilities. Instead, they rely on traditional fuels – predominately animal dung, crop residues and wood – for the majority of their energy needs. In order to tackle this problem, a key pillar of the United Nations Sustainable Energy for All (SE4ALL) initiative is to ensure universal access to modern energy services by 2030. The SE4ALL initiative provides an opportunity to build consensus on what constitutes energy access and how it can help bring people out of poverty. But if it is to succeed where others have failed, it needs to do things differently. Firstly, the initiative must move beyond viewing energy access as simply providing a grid connection. This narrow understanding ignores the complexity of energy access and fails to appreciate alternative approaches that may be more appropriate. For instance, energy is needed for multiple uses, e.g. heating, lighting, cooking, entertainment and productive activities. These uses require different forms and amounts of energy, which are determined on the basis of the specific needs and demands of individuals and communities, as well as their impacts on other resources and activities. Furthermore, access to modern energy services means more than simply availability of supply. Affordability, quantity, quality and sustainability are vital elements in determining the extent of energy access. Secondly, the SE4ALL initiative must consider the wider context and constraints within which energy access initiatives are pursued. Energy access is not an end in itself: rather, it offers the means to meet basic needs and improve livelihoods. For this to happen, diffusion of energy technologies and services must adequately deal with deeper barriers related to technologies; infrastructures (e.g. local manufacturing, installation and maintenance capabilities); markets;government policies and regulation; user practices; social norms; and cultural meaning.
Keywords: 330; Armut und Ungleichheit; Energie; Technologie und Innovation